Time-frequency characterization of the U.S. financial cycle - Fabio Verona (Bank of Finland, 2016)
Despite an increase in research – motivated by the global financial crisis of 2007-08 – empirical studies on the financial cycle are rare compared to those on the business cycle. This paper adds some new evidence to this scarce literature by using a different empirical methodology – wavelet analysis – to extract financial cycles from the data. Our results confirm that the U.S. financial cycle is (much) longer than the business cycle, but we do not find strong evidence supporting the view that the financial cycle has lengthened during the Great Moderation period.
URN:NBN:fi:bof-201605241148
Keywords: C49; E32; E44; 330